Ryby jako zasoby naturalne i jako czujące istoty żywe - Francuz, Grzegorz (Zoophilologica. Polish Journal of Animal Studies, 2025)
Fish can be considered from two perspectives: instrumental and ethical. The instrumental approach views fish as economic resources to be exploited in fisheries and aquaculture, as well as vital elements of ecosystems that play a key role in maintaining biological balance. From this standpoint, fish possess instrumental value. The ethical perspective, by contrast, emphasizes the ability of fish to feel pain, recognizing them as sentient beings with moral status. The article examines neurobiological and behavioral evidence suggesting that fish have pain receptors (nociceptors), display protective responses to harmful stimuli, and learn to avoid painful situations – indicating a basic form of consciousness and the capacity for subjective experiences of pleasure and pain. The article also considers the arguments of skeptics, who contend that fish lack sufficiently developed brain structures, such as the neocortex, which are thought to be necessary for the conscious experience of pain. From this viewpoint, the behaviors exhibited by fish may be attributed to nociceptive reflexes rather than to a conscious experience of suffering.